Keberhasilan PT PAL Indonesia Mendukung Power Projection Angkatan Laut Filipina dalam Penanganan COVID-19 Melalui Barko ng Republika ng Pilipinas Davao del Sur - Slamet Muliono Redjosari; Imroatul Fadlilah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The COVID-19 pandemic has prompted many countries to utilize all of their national resources to deal with it, including military forces. As an archipelagic country, the Philippines faced geographical and health logistics distribution challenges during the pandemic.In addressing these challenges, the BRP Davao del Sur, a Philippine warship built by PT PAL Indonesia, has played a crucial role in Military Operations Other Than War (MOOTW), particularly in the transportation and distribution of COVID-19 vaccines to remote and hard-to-reach areas. The research methodology employed in this study is qualitative descriptive, utilizing document analysis and purposive sampling interviews. The research findings indicate that PT PAL Indonesia's success not only strengthens the strategic relationship between Indonesia and the Philippines but also expands the reach of Indonesia's defense industry in the international market. The high level of trust from the Philippines has led the rice-producing nation to place another order for LPD-class ships and open new export opportunities to the Middle East, such as the United Arab Emirates. This study underscores that the national defense industry can play a crucial role in strengthening regional military capabilities and addressing non-traditional threats like pandemics. Keywords: PT PAL Indonesia, Power Projection, BRP Davao del Sur, COVID-19, Defense Industry